Technology-inspired smart learning for future education : 29th National Conference on Computer Science Technology and Education, NCCSTE 2019, Kaifeng, China, October 9-11, 2019, Revised selected papers /: 29th National Conference on Computer Science Technology and Education, NCCSTE 2019, Kaifeng, China, October 9-11, 2019, Revised selected papers. (2020) - Unknown
No abstract available